Low-frequency Observations of the Subpulse Drifter PSR J0034-0721 with the Murchison Widefield Array - McSweeney, S.; Bhat, Ramesh; Tremblay, Steven; Deshpande, A.; Ord, S. (Institute of Physics Publishing, 2017)
The phenomenon of subpulse drifting may hold the key to understanding the pulsar emission mechanism. Here, we report on new observations of PSR J0034-0721 (B0031-07) carried out with the Murchison Widefield Array at 185 MHz. We observe three distinct drift modes whose vertical drift band separations (P3) and relative abundances are consistent with previous studies at similar and higher frequencies. The drift bands, however, are observed to change their slopes over the course of individual drift modes, which can be interpreted as a continuously changing drift rate. The implied acceleration of the intrinsic carousel rotation cannot easily be explained by plasma models based on E × B drift. Furthermore, we find that methods of classifying the drift modes by means of P3 measurements can sometimes produce erroneous identifications in the presence of a changing drift rate. The "horizontal" separation between drift bands (P2) is found to be larger at later rotation phases within the pulse window, which is inconsistent with the established effects of retardation, aberration, and the motion of the visible point. Longer observations spanning at least ~10,000 pulses are required to determine how the carousel rotation parameters change from one drift sequence to the next.